Analysis of SKI Materials for the Independent Curriculum at Madrasah Aliyah and Its Development - Ummu Fitrah Widia Rahman; Martin Kustati; Nana Sepriyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
One of the most important components in learning is teaching materials, because in teaching materials there is material that is prepared completely and systematically based on learning principles that will be given by educators to students in the learning process. The aim of this research is to analyze Islamic Cultural History (SKI) teaching materials for class X MA level and their development. The research method used is Research and Development (R&D) with a 4D model, namely define, design, development and disseminate. However, in this research there are only 3 stages, namely the define stage by analyzing teaching materials, textbooks, material analysis, scope and learning outcomes, design by designing teaching materials by taking material that is not relevant to learning achievements, then adding material that is appropriate to the learning achievements then designing teaching materials that will be developed in the form of handouts, development (Development) is carried out by FGD with lecturers and postgraduate students at UIN Imam Bonjol Padang. The results of this research indicate that the main material in the class.